Mechanistic insights into the cellular effects of a novel FN1 variant associated with a spondylometaphyseal dysplasia. Issue 5 (3rd September 2018) - Cadoff, E.B.; Sheffer, R.; Wientroub, S.; Ovadia, D.; Meiner, V.; Schwarzbauer, J.E.
Abstract : Spondylometaphyseal dysplasia (SMD) is characterized by developmental changes in long bones and vertebrae. It has large phenotypic diversity and multiple genetic causes, including a recent link to novel variants in the extracellular matrix (ECM) protein fibronectin (FN), a regulator of ECM assembly and key link between the ECM and proper cell function. We identified a patient with a unique SMD, similar to SMD with corner fractures. The patient has been followed over 19 years and presents with short stature, genu varum, kyphoscoliosis, and pectus carinatum. Radiography shows metaphyseal changes that resolved over time, vertebral changes, and capitular avascular necrosis. Whole exome sequencing identified a novel heterozygous FN1 variant (p.Cys97Trp). Using mass spectroscopy, mutant FN was detected in plasma and in culture medium of primary dermal fibroblasts isolated from the patient, but mutant protein was much less abundant than wild‐type FN. Immunofluorescence and immunoblotting analyses show that mutant fibroblasts assemble significantly lower amounts of FN matrix than wild‐type cells, and mutant FN was preferentially retained within the endoplasmic reticulum. This work highlights the importance of FN in skeletal development, and its potential role in the pathogenesis of a subtype of SMD. Abstract :